Research Trends of Food Security In China: Global Governance Issues - Mei Redha, Moch. Rifqi; Sulaksono, Tunjung; Suranto, Suranto (Universitas Sultan Ageng Tirtayasa, 2025)
This study aims to broadcast globally published documents to guide the correct understanding of this context and initiate policies that the Chinese government needs. China, as one of the largest developing countries, faces the challenge of food security issues, which is an important aspect in studying the policies implemented by the Chinese government in dealing with this issue. The method used is a bibliometric analysis approach with data sources from the Scopus database. The analysis tools are CiteSpace and VOSviewer. This study found that global research trends on food security issues have influenced the interests of researchers worldwide. This is evidenced by the high number of recently published documents. Several research themes require further evaluation, including China's land protection and food policy. The implications of these findings also contribute to the formulation of China's future policies. Responsiveness to global change is also an important point to consider.